2017
DOI: 10.1038/s41467-017-01804-w
|View full text |Cite
|
Sign up to set email alerts
|

A transcribed enhancer dictates mesendoderm specification in pluripotency

Abstract: Enhancers and long noncoding RNAs (lncRNAs) are key determinants of lineage specification during development. Here, we evaluate remodeling of the enhancer landscape and modulation of the lncRNA transcriptome during mesendoderm specification. We sort mesendodermal progenitors from differentiating embryonic stem cells (ESCs) according to Eomes expression, and find that enhancer usage is coordinated with mesendoderm-specific expression of key lineage-determining transcription factors. Many of these enhancers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 68 publications
6
63
0
Order By: Relevance
“…Recent studies have shown that the lncRNAs Bvht and Fendrr play important roles in proper cardiac differentiation (Grote et al, 2013;Klattenhoff et al, 2013). In keeping with the recently published paper by Alexanian et al (2017), we report that a lincRNA, termed linc1405 or Meteor, is expressed in fetal heart tissue and is a regulator of cardiac lineage commitment. First, knockdown or complete depletion of linc1405 could significantly repress the ability of ESCs to differentiate into CMs in both EB differentiation and CM differentiation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recent studies have shown that the lncRNAs Bvht and Fendrr play important roles in proper cardiac differentiation (Grote et al, 2013;Klattenhoff et al, 2013). In keeping with the recently published paper by Alexanian et al (2017), we report that a lincRNA, termed linc1405 or Meteor, is expressed in fetal heart tissue and is a regulator of cardiac lineage commitment. First, knockdown or complete depletion of linc1405 could significantly repress the ability of ESCs to differentiate into CMs in both EB differentiation and CM differentiation.…”
Section: Discussionsupporting
confidence: 87%
“…Linc1405 is required for cardiac differentiation and significantly affects the cardiac gene network by functionally interacting with Eomes and targeting Mesp1. Shortly after this article's online publication, it was brought to our attention that similar results in ESCs have recently been reported by Alexanian et al (2017), who described regulation of Eomes-dependent mesendodermal specification and cardiac differentiation by an enhancer-associated lncRNA they named Meteor (MesEndoderm Transcriptional Enhancer Organizing Region). Our further mechanistic studies revealed that exon 2 of linc1405 specifically partners with Eomes, WDR5, and GCN5 to regulate histone modification of the enhancer region of the Mesp1 gene, thus controlling Mesp1 transcription and cardiac lineage commitment.…”
Section: Introductionsupporting
confidence: 62%
“…While the association between elincRNA transcription and enhancer activity is relatively well established, whether the molecular mechanisms underlying their functions depend on their transcript sequences has not yet been equivocally demonstrated. Notably, consistent with the absence of nucleotide conservation at their exons (Marques et al, 2013), many elincRNA functions appear to rely on transcription alone (Alexanian et al, 2017;Hsieh et al, 2014;Lai et al, 2013;Li et al, 2013;Yoo et al, 2012).…”
Section: Introductionmentioning
confidence: 88%
“…Review (Alexanian et al, 2017) and MALAT1 (Aparicio-Prat et al, 2015). Cells carrying promoter deletions display strongly reduced lncRNA expression levels, with allelic deletion efficiencies up to 60% in unsorted cells (Pulido-Quetglas et al, 2017).…”
Section: Genomic Deletionmentioning
confidence: 99%